Methodical issues of evaluation of efficiency of construction enterprise - Hoiko, A. (Ways to Improve Construction Efficiency, 2022)
The article is devoted to the evaluation of the efficiency of production activities of a construction company. The article analyzes modern approaches to the essence of the concept of "efficiency of production activities", according to which it is proposed to understand the positive or negative results of the enterprise, characterized by a set of indicators that summarize the ratio of final results to costs. The article examines the theoretical and methodological approaches to assessing the economic efficiency of production in modern economic conditions, related to the definition of the main aggregate indicators for a comprehensive analysis of enterprises. Various forms of manifestation of economic efficiency that occur in the conditions of practical management are analyzed. Indicators assessing the efficiency of production and economic activities of the enterprise are considered. The essence of the used efficiency indicators is revealed, which differ depending on the purposes of the analysis and can be classified on four groups: indicators of an estimation of an economic condition, efficiency of industrial and economic activity, investment activity and social efficiency. The table with the generalizing indicators of efficiency of work of the enterprise is resulted and necessity of their use for an estimation of efficiency of work of the enterprise is proved. The two-level system of indicators of production efficiency, including the upper and lower level, is analyzed. The upper level includes performance indicators of the enterprise as a whole, reflecting the overall level of efficiency achieved at the enterprise. The lower level includes own indicators of the use of resource factors of production, which reveal the reasons that determine the level of efficiency of the enterprise and indicate the direction of managerial influence on its improvement. It is established that the efficiency of production activities of the enterprise is a complex characteristic, to determine which should use a set of different criteria for assessing its effectiveness.